2018
DOI: 10.18517/ijaseit.8.4-2.6794
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary School Students Perspective on Kolb-based STEM Module and Robotic Prototype

Abstract: The aim of this paper is to assess students' perceptions of their competency and interests in Science, Technology, Engineering and Mathematics (STEM) throughout Malaysia. These perceptions are obtained during and after they were engaged in using a STEM module and building a robotic prototype that was in line with the STEM teachers' specification, and was conducted at the National Science Centre, Malaysia. This activity was undertaken because the target ratio for the number of students enrolling in STEM program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
(14 reference statements)
2
12
0
Order By: Relevance
“…According to Smith and Rayfield (2017), sequenced instruction with the foundation of experiential learning theory may help educators to more effectively integrate STEM concepts for students. A study by Zainal et al (2018) showed that the STEM module and robotic prototype based on Kolb's experiential learning increased the learning efficiency of students. Using experiential learning in STEM studies also allowed students to work on meaningful hands-on activities (Pappas et al, 2018).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…According to Smith and Rayfield (2017), sequenced instruction with the foundation of experiential learning theory may help educators to more effectively integrate STEM concepts for students. A study by Zainal et al (2018) showed that the STEM module and robotic prototype based on Kolb's experiential learning increased the learning efficiency of students. Using experiential learning in STEM studies also allowed students to work on meaningful hands-on activities (Pappas et al, 2018).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Multimedia has remarkable impact on learning (Zainal et al, 2018;Gabarre et al 2018;Ahmad et al 2016;Azizul & Din, 2016). It has emerged in various form of recourses and equipment which can be use to aid the instructor and learner effort in ensuring effective learning environment (Ahmad et al, 2016).…”
Section: Multimedia Instruction (Mi)mentioning
confidence: 99%
“…2) The present bending direction angle α, the bending angle β and the length L is determined using equations (5) and (6). The current arm end's coordinates X c , Y c , Z c are obtained using these calculated values.…”
Section: Control Proceduresmentioning
confidence: 99%
“…Such population differences have become more apparent every year, raising the concerns of various professional community from aspects of engineering, healthcare and social sciences. Today, many studies have shown a wide adoption of robot technology used in manufacturing [1], agriculture [2], communication [3], and education [4,5]. In the line of 4IR, there is demand for one system that can control, communicate and integrate different robots regardless of their types and specifications.…”
Section: Introductionmentioning
confidence: 99%